Effectiveness of Visual Distraction In Reducing Pain Intensity During Intravenous Insertion Among Children Aged 3–5 Years - Tane, Reisy; Barus, Dewi Tiansa (Jurnal Pinang Masak, 2026)
Introduction: A common trigger for discomfort, particularly in pediatric inpatients, is intravenous (IV) catheter placement. Intravenous procedure can cause tissue damage that can cause pain and anxiety in toddlers. The objective of this study is to assess the effectiveness of virtual distraction in reducing pain intensity during IV line insertion in children. Methods: This research is quantitative research, with a quasi-experimental pre-post design. Respondents were selected using a purposive sampling method with the following inclusion criteria: children aged 3-5 years, with an IV installed, and willing to participate as research respondents. Exclusion criteria were children with complications such as phlebitis, decreased consciousness, or those receiving analgesic drugs. The sample size was 25 children. Data analysis involved univariate and bivariate approaches. Univariate analysis includes normality tests, especially the Shapiro-Wilk test, where the p-value is expected to be less than α (0.05), and bivariate analysis uses the Wilcoxon. Results: The results explain that p value 0.00 it’ means there is a significant difference between the pre and post test. Based on the research results, it was found that pain during IV insertion was significant. Children who received visual distraction therapy experienced less pain than before receiving distraction therapy. Conslusion: Therefore, based on the results of this study, it is recommended that it be implemented in health services, especially in pediatric nursing rooms.